2021
DOI: 10.1292/jvms.21-0086
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gel pad thickness on the evaluation of skin structures using ultrasonography in normal dogs

Abstract: Gel pads are commonly used in skin ultrasonography; however, the effects of their thickness are unknown. This study investigated the effects of pad thickness on measurements of skin thickness in 10 beagle dogs. Sonograms to measure neck skin thickness were captured without pads and using pads with thicknesses of 3, 5, 10, and 20 mm. Without pads, acoustic shading was observed due to air bubbles in the coupling gel. With 20-mm pads, echogenic artifacts were observed on the skin surface.Entry echo with 20-mm pad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Therefore, in the clinical observation of superficial tissue, gel pads are often used to increase the near-field distance and improve the permeability of media to achieve ultrasonic resolution in superficial tissue. Studies have shown that gel pads are superior to ordinary liquid coupling gels through the transmission of high-frequency sound energy, and with coupling gels, tiny bubbles are contained in liquid couplings, possibly causing ultrasonic artefacts and affecting the visibility of superficial skin structures [ 12 , 13 ]. Furthermore, some masses in superficial tissues are raised to the skin surface, irregularly shaped or located in uneven skin sites, which creates contact difficulty between the ultrasound probe and tissue, limiting the image display range.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the clinical observation of superficial tissue, gel pads are often used to increase the near-field distance and improve the permeability of media to achieve ultrasonic resolution in superficial tissue. Studies have shown that gel pads are superior to ordinary liquid coupling gels through the transmission of high-frequency sound energy, and with coupling gels, tiny bubbles are contained in liquid couplings, possibly causing ultrasonic artefacts and affecting the visibility of superficial skin structures [ 12 , 13 ]. Furthermore, some masses in superficial tissues are raised to the skin surface, irregularly shaped or located in uneven skin sites, which creates contact difficulty between the ultrasound probe and tissue, limiting the image display range.…”
Section: Discussionmentioning
confidence: 99%